2009
DOI: 10.1007/s00114-009-0509-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium thermodynamics and maximum entropy production in the Earth system

Abstract: The Earth system is maintained in a unique state far from thermodynamic equilibrium, as, for instance, reflected in the high concentration of reactive oxygen in the atmosphere. The myriad of processes that transform energy, that result in the motion of mass in the atmosphere, in oceans, and on land, processes that drive the global water, carbon, and other biogeochemical cycles, all have in common that they are irreversible in their nature. Entropy production is a general consequence of these processes and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 155 publications
(161 reference statements)
7
123
0
Order By: Relevance
“…In the real climateṠ ver can be thought of as the entropy production due to the sum of latent and sensible heat fluxes at the surface (Kleidon, 2009) and, to a minor extent, turbulent dissipation of kinetic energy. Lucarini et al (2011) have shown thatṠ hor is a lower bound of entropy production due to dissipation of kinetic energy.…”
Section: The Modelmentioning
confidence: 99%
“…In the real climateṠ ver can be thought of as the entropy production due to the sum of latent and sensible heat fluxes at the surface (Kleidon, 2009) and, to a minor extent, turbulent dissipation of kinetic energy. Lucarini et al (2011) have shown thatṠ hor is a lower bound of entropy production due to dissipation of kinetic energy.…”
Section: The Modelmentioning
confidence: 99%
“…Onsager's principle, and variations thereof, have been useful in describing the existence and stability of abiotic and biotic dissipative systems on Earth (Lorenz, 1960;Paltridge, 1979;Ulanowicz and Hannon, 1987;Swenson, 1989;Kleidon and Lorenz, 2005;Michaelian, 2005;Martyusheva and Seleznev, 2006;Kleidon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules, in the presence of water, are extraordinarily rapid at dissipating the high energy photons to heat. It is then plausible that life arose as a catalyst for absorbing sunlight at the surface of the shallow seas, dissipating it into heat and, thereby promoting still other irreversible processes such as the water cycle (evaporation/rain), and wind and ocean currents, all of which contribute to the entropy production of the biosphere (Peixoto et al, 1991;Kleidon 2009). This suggests a thermodynamic imperative for an origin of life which can be related to its thermodynamic function of entropy production (Michaelian, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has gained in prominence with the recent rise of Maximum Entropy concepts in physics, especially in the earth sciences (Whitfield 2005; Kleidon 2009Kleidon , 2010. It builds on the statistical mechanics foundation of thermodynamics, and seems therefore plainly incompatible with Georgescu-Roegen's critique of Boltzmann.…”
Section: The Problem Of the Contextuality Of Entropy: Fertile Ground mentioning
confidence: 99%
“…Thus, the maximum power principle is treated as a correlate of the MEP principle. This view has been concisely developed by Kleidon (2009Kleidon ( , 2010 and states that open non-equilibrium systems such as the earth system will always manifest the tendency to approach the maximum entropy state, which is defined as the macroscopic state which is most probable, given energy and mass-balance constraints. This tendency is empirically complex because the respective manifold processes proceed in vastly different time scales.…”
Section: Fig 3: Observer Independent and Observer Relative Entropymentioning
confidence: 99%